The Dynamics of Law Enforcement in Indonesia: According to Donald Black's Legal Discrimination Theory - Dwi Rahmawati; Hikmatul Abibah (Pattimura Legal Journal)
Introduction: This article analyzes the justice crisis of several cases of law enforcement due to legal stratification Donald Black`s Teheory and explains integrative steps to overcome the problem of law enforcement discrimination in Indonesia.